Prevalence of prehypertension and associated cardiovascular risk profiles among prediabetic Omani adults - Duttagupta Kalyan; Bhargava Kamlesh; Al-Shafaee Mohammed; Ganguly Shyam (BMC, 2008)
Abstract Background The importance of prediabetes and prehypertension has been demonstrated in several studies especially for primary prevention of CVD. A recent community based cross-sectional study revealed that 40.9 percent Omani adults are prediabetics. This study was undertaken to estimate the prevalence of prehypertension and associated cardiovascular risk profiles in prediabetics. To best of our knowledge, this is the first report on this subject. Methods The study included 327 confirmed pre-diabetic Omani adults, who were analysed for their demographic, metabolic and behavioral characteristics. These characteristics were compared between the three different blood pressure groups to determine the CVD risk factors. Univariate and step-wise multiple logistic regression methods were used to carry out the analysis of the data. Results In this study, the prevalence of prehypertension was 54.1 percent. Males were at higher risk of developing prehypertension as compared to females (OR = 2.30, 95% CI: 1.21, 4.38; P < 0.01). The individuals with higher BMI have two fold more risk of developing prehypertension (OR = 2.25, 95% CI: 1.26, 4.02; P < 0.01). The increased level of OGT enhanced the risk of developing prehypertension (OR = 1.26, 95% CI: 1.06, 1.50; P < 0.01). Conclusion A high prevalence of prehypertension (54.1%) exists in this study population. The major determinants of prehypertension in these prediabetic subjects were male gender, increasing dysglycemia and BMI. Appropriate intervention strategies have been suggested.